Tax Sanctions and Tax Office Services Terhadap Kepatuhan Wajib Pajak Orang Pribadi Usaha di Kabupaten Pohuwato - Kartini Muslimin; Sulfianty Sulfianty (Al-Buhuts, 2020)
Abstract This study uses primary data with a structured interview research method in the form of questionnaires distributed to respondents and the measurement scale is the Likert scale. The population of this research is 373 individual taxpayers who own a business. The independent variable in this study is Tax Sanctions (X1) and Tax Office Services (X2), while for the dependent variable is the Business Individual Taxpayer Compliance. The method of analysis in this research is multiple regression analysis method and hypothesis testing used is the T test and F test. The results showed that partially Tax Sanctions and Tax Office Services had a positive and significant effect on business individual taxpayer compliance with the value of T-count for X1 of 4.522 and X2 of 8.401 greater than T-table of 1.992 for both variables, as well as the F test where The value of X1 and X2 simultaneously Fcount of 287.479> from Ftable 3.12 with a significance value for the T test and F test of 0.000. The magnitude of the influence of X1 and X2 on Y is 88.3%, the remaining 11.7% is influenced by other variables. Keywords: Tax Sanction; Tax Office Services; and Compliance of Business WP OP